The era of reference genomes in conservation genomics - Formenti, Giulio; Theissinger, Kathrin; Fernandes, Carlos; Bista, Iliana; Bombarely, Aureliano; Bleidorn, Christoph; Ciofi, Claudio; Crottini, Angelica; Godoy, José A.; Höglund, Jacob; Malukiewicz, Joanna; Mouton, Alice; et al. (Elsevier, 2022)
Conservation efforts need to account for genomic diversity to optimize management strategies. Accounting for genomic diversity will aid in maintaining population viability and preserving adaptive potential to respond to environmental change. The availability of reference genomes will provide a solid, quantitative, and comparable foundation for biodiversity assessments, conservation, management, and restoration.